Structural and Electrical Properties of NASICON Type Solid Electrolyte Nanoscaled Glass-Ceramic Powder by Mechanical Milling for Thin Film Batteries - Patil, Vaishali; Patil, Arun; Yoon, Seok-Jin; Choi, Ji-Won (AMER SCIENTIFIC PUBLISHERS, 2013)
During last two decades, lithium-based glasses have been studied extensively as electrolytes for solid-state secondary batteries. For practical use, solid electrolyte must have high ionic conductivity as well as chemical, thermal and electrochemical stability. Recent progresses have focused on glass electrolytes due to advantages over crystalline solid. Glass electrolytes are generally classified into two types oxide glass and sulfide glass. Oxide glasses do not react with electrode materials and this chemical inertness is advantageous for cycle performances of battery. In this study, major effort has been focused on the improvement of the ion conductivity of nanosized LiAlTi(PO4)(3) oxide electrolyte prepared by mechanical milling (MM) method. After heating at 1000 degrees C the material shows good crystallinity and ionic conductivity with low electronic conductivity. In LiTi2(PO4)(3), Ti4+ ions are partially substituted by Al3+ ions by heat-treatment of Li2O-Al2O3-TiO2-P2O5 glasses at 1000 degrees C for 10 h. The conductivity of this material is 1.09 x 10(-3) S/cm at room temp. The glass-ceramics show fast ion conduction and low E-a value. It is suggested that high conductivity, easy fabrication and low cost make this glass-ceramics promising to be used as inorganic solid electrolyte for all-solid-state Li rechargeable batteries.
Keywords: LITHIUM-ION BATTERIES; CONDUCTIVITY